EVALUASI SISTEM REAL TIME ONLINE DALAM PROGRAM PENERIMAAN PESERTA DIDIK BARU DI DINAS PENDIDIKAN KOTA YOGYAKARTA - Firlani, Heru Dyah (Spektrum Analisis Kebijakan Pendidikan, 2021)
This study aims to describe the evaluation of the Real-time Online system in the new student admission program at the Yogyakarta City Education Office. The method in this study is a qualitative descriptive study with the CIPP evaluation model. The data collection techniques used in this study are documentation, interviews, and observations. The research data were analyzed using the Miles and Huberman model. The validity test of the data used triangulation of sources and techniques. The results of the study show that: (1) Context aspect, policies for implementing the new student admission program with the Real-Time Online system in the Yogyakarta City Education Office are relevant and have referred to Yogyakarta Mayor regulation number 24 of 2018. (2) Input aspect, the availability of human resources has been fulfilled. The completeness and feasibility of infrastructure are still lacking, such as a network that had problems. (3) The process aspect, the implementation of the program is by following the guidelines for the admission of new students to the education, it is being objective, accountable, transparent, and non-discriminatory. (4) Aspects of results, the data of students who register with the capacity for elementary schools have been met, however, for junior high school there are still empty seats. Â Keywords: real time online system, the new students admissionÂ  Â